Computer And Computing Technologies In Agriculture, Volume I First IFIP TC 12 International Conference on Computer and Computing Technologies in Agriculture (CCTA 2007), Wuyishan, China, August 18-20, 2007 - Li, Daoliang; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Web-based Expert System of Wheat and Corn Growth Management -- Multicast in Mobile Ad-Hoc Networks -- GIS Combined with MCE to Evaluate Land Quality -- Control Systems in our Daily Life -- An Improved Fast Brain Learning Algorithm -- Role's Function in CMS.-Forecast Research of Droplet Size Based on Grey Theory -- Crop Disease Leaf Image Segmentation Method Based on Color Features.-.
Keywords: COMPUTER SCIENCE; SOFTWARE ENGINEERING; COMPUTER SIMULATION; BIOINFORMATICS; COMPUTER SCIENCE; SPECIAL PURPOSE AND APPLICATION-BASED SYSTEMS; SIMULATION AND MODELING; COMPUTATIONAL BIOLOGY/BIOINFORMATICS.